Pomiędzy okaleczeniem a autorską strategią. Wpływ cenzury na twórczość Luisa Garcíi Berlangi - Aleksandrowicz, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article presents the complex impact of Francoist censorship on Luis García Berlanga’s works. In films shot during General Francisco Franco’s dictatorship, the Spanish director developed a number of auteur strategies that allowed him to express veiled criticism of the regime, which escaped the attention of censors. The game with censorship requirements became characteristic of Berlanga’s works and influenced their reception by domestic audiences, who interpreted some scenes as political allusions not intended by the author. The analysis also shows the impact of censor interference in the final form of some films and attempts at eliminating their controversial message, as well as cases of delayed Spanish distribution or the realisation of the director’s boldest projects, which were premiered or could only be shot after the fall of the dictatorship.